1982
DOI: 10.1002/j.1460-2075.1982.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

SV40 virions and viral RNA metabolism are associated with cellular substructures.

Abstract: Nuclear matrices were prepared by DNase and high salt extraction of SV40‐infected epithelial monkey cells. The matrices retain the majority of SV40 virions. This conclusion is based on electron microscopic observations of the occurrence of encapsidated viral DNA that is resistant to DNase digestion and on the analysis of viral proteins by gel electrophoresis. Pulse labeled SV40 RNA is also associated with the nuclear matrix (less than 15% of the viral RNA is removed by DNase and high salt). Pulse‐chase experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The E7 protein, like most nuclear matrix proteins, was removed from the complete matrix by 2 M NaCl extraction and was not retained with the core filaments. Previous studies have localized the viral oncoproteins simian virus 40 large tumor antigen and adenovirus Ela (which have many properties in common with E7) to a nuclear matrix structure prepared with high salt (52,53). In the present work, HPV-16 E7 is localized on a nuclear matrix prepared with moderate salt but removed by higher salt concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…The E7 protein, like most nuclear matrix proteins, was removed from the complete matrix by 2 M NaCl extraction and was not retained with the core filaments. Previous studies have localized the viral oncoproteins simian virus 40 large tumor antigen and adenovirus Ela (which have many properties in common with E7) to a nuclear matrix structure prepared with high salt (52,53). In the present work, HPV-16 E7 is localized on a nuclear matrix prepared with moderate salt but removed by higher salt concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…To localize the subnuclear distribution of p53, nuclei were treated with DNase and salt to remove -95% of the DNA and histones. This fractionation yields a solubilized chromatin fraction and leaves behind the skeletal framework of the nucleus, the nuclear matrix (Berezney and Coffey, 1974;Ben-Ze'ev et al, 1982;Capco et al, 1982). We compared the relative amount of p53 in the solubilized chromatin fraction and in the nuclear matrix fraction in SV40-transformed and methylcholanthrene-transformed fibroblasts by the immunofluorescence and immunoprecipitation procedures as used above.…”
Section: Subnuclear Localization Ofp53 In Transformed Fibroblastsmentioning
confidence: 99%
“…Although the validity of comparisons between X. laevis oocytes and somatic cells can be questioned, it should be noted that Graessman et al (13) previously showed that when large, but not In infected cells the vast majority of both VP-1 and the L-T antigen are located in the nucleus, as determined both by indirect immunofluorescent antibody staining (12) and by immunoprecipitation of detergent extracts of the cytoplasmic and nuclear portions of radioactively labeled cells (1,28). It was thus rather surprising that only a relatively small proportion of the VP-1 and VP-3 capsid proteins were found in the oocyte nucleus.…”
mentioning
confidence: 99%